How Does Entrepreneurial Self-Efficacy Influence Innovation Behavior? Exploring the Mechanism of Job Satisfaction and Zhongyong Thinking - Wei, Jiangru; Chen, Yuting; Zhang, Yamin; Zhang, Jing (Frontiers in Psychology, 2020)
Innovation behavior for entrepreneurship is known as a driving force to obtain competitive advantages. As a key quality for entrepreneurial success, the mechanism of entrepreneurial self-efficacy acting on innovation behavior remains further verification, which has led to the primary objective of this paper via applying the Goal Self-concordance Theory, as well as to further build a theoretical model. 249 samples of Chinese entrepreneurs have been empirically analyzed in this study, contributing to the following findings. Firstly, entrepreneurial self-efficacy has significantly positive effects on entrepreneurial innovation behavior. Secondly, job satisfaction plays a mediating role between entrepreneurial self-efficacy and innovation behavior. Thirdly, Zhongyong thinking moderates the relationship between entrepreneurial self-efficacy and job satisfaction. The research results might deliver great value in cultivating entrepreneurial self-efficacy, encouraging positive entrepreneurial attitude, enhancing job satisfaction, and ultimately inspiring innovation behaviors.